Quality happens through people : learning how to help it happen (AT&T Corporate Quality Office [S.l.]US, 1994)
Presents employees who, while struggling with organizational change that threatened their jobs and business, reorganized and accelerated progress. Highlights factors which contributed to their success including: direct and frequent communication; thoughtful and deliberate planning; and, strategies for supporting and empowering employees, such as, mentoring, coaching, celebration and recognition.
Located in the Learning Resource Centre